Efektivitas Penggunaan Metode Pembelajaran Mind Mapping Terhadap Peningkatan Hasil Belajar Fikih Siswa - Fitriyati, Diyah; Karyanto, Umum Budi (Indonesian Journal of Islamic Elementary Education, 2021)
One method that can invite students to be active at the same time according to the characteristics of theFiqh material is the Mind Mapping learning method. This study aims to: 1. Determine whether there are differences in fiqh learning outcomes between students who are taught using mind mapping methods and conventional methods. 2. Testing the effectiveness of using the mind mapping method in improving fiqh learning outcomes for fourth grade students. This research is intended to provide educational insights (theoretical), as well as learning reference materials for related parties (practical). This study uses a quantitative approach with a quasi-experimental type. The data collection technique is a written test. Written tests were in the form of pre-test and post-test, which were then analyzed by independent sample t-test and N-Gain test. From the independent sample t test shows that sig. 2 tailed is 0.000 or <0.05.The average post-test score for the experimental class was 90.00 and the control class 80.68. From the N-Gain test, it is known that the average N-Gain value in the experimental class is 73.2% (high effectiveness category), while for the control class it is 45.5% (medium effectiveness category). So it can be concluded that the application of the mind mapping method is effective in improving Fiqh learning outcomes for fourth grade students of MI Gondang.